'A Musical Bouquet for the Ladies': Gendered Markets for Printed Music in Eighteenth‐Century England. - Bridge, Dominic James Ruggier (Journal for Eighteenth-Century Studies, 2023)
This article explores how music publishers recruited the gendered expectations of musical practice to market their scores to male and female audiences. It shows how the graphic and textual elements of title pages and prefaces were used as promotional material and reveals how publishers encoded gendered representations of music making into their printed editions in order to navigate the social worlds in which they were consumed. The opening section will discuss how music publishers appropriated images of courtship scenes on the title pages of keyboard tutors (to market their scores towards young women) and explain how prefaces could be used to placate the feminine associations of musical practice to help publishers sell to a male audience. The discussion will then turn to the concept of gift giving, explaining how graphic imagery could be used to place the score at the centre of elite romantic interactions, modelling expected commercial behaviours.